องค์ประกอบธาตุในฝุ่นละอองขนาดเล็กกว่า 2.5 ไมครอนในเขตกรุงเทพมหานคร - รพีพัฒน์ เกริกไกวัล (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The small size air borne particulates were sampling by using dichotomous air sampler. The level of small size PM2.5 in Bangkok sites, was higher than in control site. The ratio of PM2.5 to PM10 is more than 50%. During dry season, the level of particulates in Dindang, Phayathai and Phuttamonthol Sai 2 were higher than in wet season. Dindang site represented the roadside atmosphere had average PM2.5, 65.35+-18.7 micro g./m3 in wet season and 129.56+-38.9 micro g./m3 in dry season. Phayathai site represented the ambient atmosphere had average PM2.5, 27.71+-16.95 micro g./m3 in wet season and 62.63+-30.3 micro g./m3 in dry season and Phuttamonthol Sai 2, the control area, had average PM2.5, 14.21+-1.87 micro g./m3 in wet season and 32.40+-9.9 micro g/.m3 in dry season. Coefficient of relation between PM2.5 and PM10 was 0.979. The level of PM10 could reflect the trend of PM2.5 quantity in atmosphere. The major elements in PM2.5 were carbon, sulfur, and potassium. PM2.5 to 10 micron consists of ferrous, silica, and calcium. Quantitative of trace element composition in PM2.5 has Potassium 1.3892 micro g./m3, Zinc 0.4529 micro g./m3, Manganese 0.1518 micro g./m3, Lead 0.0576 micro g./m3 and copper 0.0095 micro g./m3. Roadside atmosphere area has major element composition higher ambient area and control site respectively. However the variation of element composition was not directly related to the loading of particulate level. It could depend on the source apportionment and type of pollution rather than the concentration of particulate matters